Online “iDentity” Formation and the High School Theatre Trip - Richardson, John (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
Over the years that I have taken secondary school students to the theatre, the the digital revolution has moved through schools, classrooms, and even theatres, calling into question my goal of contributing positively to students’ identity formation through exposure to live plays. Responding to calls to examine the ways in which young people’s online and offline lives are interwoven, a one-year qualitative case study of student theatregoers suggests that online settings feature prominently in students’ identity formation and that non-digital school experiences such as the theatre trip are often experienced in light of students’ digital lives. Traditional events such as a trip to the theatre are influenced by and combined with online experiences to contribute to a new “iDentity” formation.